Pressure correction for the computation of nitrate concentrations in seawater using an in situ ultraviolet spectrophotometer. (19th September 2017) - Sakamoto, Carole M.; Johnson, Kenneth S.; Coletti, Luke J.; Jannasch, Hans W.
Abstract: The most accurate calculation of nitrate concentration from the ultraviolet (UV) absorption spectrum of seawater requires that the absorption signal due to bromide in seawater be removed before nitrate concentrations are computed. Recent work suggests that the UV absorption spectrum of bromide in seawater has a pressure dependence. Neglect of this signal could add a bias when nitrate concentrations at high pressure are computed from UV measurements. Laboratory tests were conducted to determine the pressure dependence of the bromide absorption in seawater. Our results confirm the existence of a pressure coefficient in the bromide spectrum. The percentage change in bromide molar absorptivity is wavelength and temperature independent. The effect of pressure on the absorptivity of sea salt ( E SW ), which is dominated by bromide ion, can therefore be calculated as E SW pressure = E SW 1 dbar ∗ ( 1 – 0.0 26 ∗ Pressure ( dbar ) / 1000 ) The correction amounts to an error of around 0.95 μM nitrate at 1000 dbar. The pressure correction should be used in the calculations of nitrate concentrations from UV absorption spectra at high pressures.